ENGLISH VARIETIES - Rasuna Talib (Jurnal Inovasi, 2011)
The aim of this article is to describe both theory and specimens of the English varieties as stated by Mc.Arthur, such as nativized, decoratives, domesticated, and fractured English. Some data were extracted from authentic materials: magazine, newspaper, consumer of goods, clothing, etc. Decorative English refers to the English variety where English words are only used in this variety for specific purposes or the reason or prestige product; Domesticated English refers to the English variety where it takes place inside the native language Domesticated and borrowing EnglishThe words fit perfectly into existing language system because they represent concepts and items for which no prior word existed and it is permanently words used by country which need them. Indonesia, for example, has been a great deal of borrowing words, such as in medical, advertisement, economy, banking, etc. In this matter, we also find many English words which are used by Indonesia temporally, what we called borrowing word. And the last one is fractured English, that is the misuses of English words and it has been discovered in advertisement, hotel notices, restaurant menus, etc.